Systematic Literature Review: Regulatory Uncertainty and Its Impact on Hospital Project Performance - Jasran Asya; Yohanes Calvinus; Oei Fuk Jin (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
Hospital infrastructure projects are inherently complex due to their exposure to dynamic healthcare regulations, fiscal constraints, long-term financing arrangements, and technological innovation. Regulatory uncertainty has emerged as a critical institutional factor influencing project performance; however, its impact within hospital projects remains insufficiently synthesized. This study employs a Systematic Literature Review (SLR) following PRISMA 2020 guidelines to analyze 19 peer-reviewed studies published between 2022 and 2026 that examine the relationship between regulatory uncertainty and project performance. The findings indicate that 42.1% of the reviewed studies report a positive association between regulatory uncertainty and cost overruns, while 36.8% identify significant links to schedule delays. The effect on quality outcomes is non-linear: some studies reveal quality deterioration due to time and budget pressures, whereas others demonstrate that stable and stringent regulatory frameworks enhance technical quality and accountability. These mixed findings suggest a regulatory–performance paradox, where regulatory volatility increases risk and inefficiency, but regulatory stability strengthens governance and long-term project sustainability. This study proposes a conceptual framework positioning regulatory uncertainty as an institutional mediator between governance structures, financing mechanisms, and hospital project performance, offering implications for policy design and risk management in healthcare infrastructure development.